IDNLearn.com connects you with a community of experts ready to answer your questions. Our community is here to provide the comprehensive and accurate answers you need to make informed decisions.

Which of the following expressions is equal to -x^2 - 81? A. (-x-9i)(x+9i) B. (-x+9i)(x-9i) C. (-x-9i)(x-9i) D. (x+9i)(x-9i)

Sagot :

I think C. (-x-9i)(x-9i)

You can multiply them to get:
(-x-9i)(x-9i)=[tex]- x^{2} +9xi-9xi+81 i^{2} [/tex]=
remembering that: [tex]i= \sqrt{-1} [/tex] so that:
[tex] i^{2} =-1[/tex]
Finally:
[tex]- x^{2}+81 i^{2} [/tex]=[tex]= -x^{2} -81[/tex]